1999
DOI: 10.1161/01.str.30.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Acute Caudate Vascular Lesions

Abstract: Background and Purpose-We sought to evaluate demographic features, risk factors, clinical profiles, and behavioral abnormalities in patients with caudate lesion, either with infarct or with hemorrhage involving the caudate nucleus. Methods-We studied all patients with acute caudate stroke confirmed by CT or MRI who were admitted to our stroke unit over a 5-year period. A database containing risk factors, clinical features, type and mechanism of stroke, and caudate vascular territories was analyzed. Results-Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
105
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(121 citation statements)
references
References 35 publications
(65 reference statements)
10
105
0
5
Order By: Relevance
“…Contrasts were used to test for differences between the levels of the factor stimulation. The results of the line bisection task were analyzed by a 4 ϫ 3 factor design using the variables stimulation (right OFF/left OFF, right ON/left OFF, right OFF/left ON, and right ON/left ON) and length of the line (8,16, and 24 cm). Again, contrasts were used to test for differences between the levels of the factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasts were used to test for differences between the levels of the factor stimulation. The results of the line bisection task were analyzed by a 4 ϫ 3 factor design using the variables stimulation (right OFF/left OFF, right ON/left OFF, right OFF/left ON, and right ON/left ON) and length of the line (8,16, and 24 cm). Again, contrasts were used to test for differences between the levels of the factors.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 -10 Various studies have documented that lesions restricted to the right basal ganglia lead to an asymmetry in space exploration and a failure to react or respond to stimuli located in the contralateral hemispace. 2,[11][12][13][14][15][16][17][18] Most of these studies examine patients with neglect as a consequence of stroke and it has been controversial if hemispatial neglect following subcortical lesions are the consequence of associated cortical dysfunction not visible by structural computer tomography or conventional magnetic resonance imaging (MRI). 15,19,20 In support of this hypothesis, several studies have shown cortical hypoperfusion in patients with neglect associated with subcortical stroke using MR perfusion-weighted imaging or single photon emission computed tomography (SPECT).…”
mentioning
confidence: 99%
“…Ãzci et al reported that this artery supplies blood to important areas, such as the medial portion of orbitofrontal area, head of the caudate nucleus, anterior portion of putamen, external segment of globus pallidus, and anterior limb of the internal capsule [2]. We would just like to add another very important brain area where this important artery also supplies blood and which is the nucleus accumbens [1,3]. This nucleus is a major component of the ventral striatum and speciWcally the area of continuity between the head of the caudate nucleus and the putamen [5].…”
Section: Dear Editormentioning
confidence: 99%
“…[1][2][3] Hypertension can alter the vascular structure, mechanics, and function of small arteries and arterioles. 4,5 These changes disturb the structure and function of microcirculation, resulting in increased vascular resistance and reduced blood flow through the microvessels.…”
mentioning
confidence: 99%